GAYA BELAJAR SISWA KELAS V DI TINJAU DARI HASIL BELAJAR MATEMATIKA SD NEGERI 26 SINTANG - Wedyawati, Nelly; Milu, Rupina (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to describe dominant learning styles, supporting factors, and the teacher’s role in adapting instructional strategies. The research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. The subjects consisted of 21 students selected through purposive sampling and a fifth-grade teacher. Data analysis followed the interactive model of Miles and Huberman, including data collection, reduction, narrative display, and conclusion drawing, with triangulation of techniques and sources to ensure validity. The findings revealed that: (1) the auditory learning style was the most dominant, with five out of nine students categorized in this group, showing higher average mathematics scores compared to visual and kinesthetic learners; (2) supporting factors included students’ interest, motivation, independent learning habits, self-regulation, teacher strategies, learning media, classroom environment, and remedial support; and (3) teachers played a crucial role in adapting instructional methods through varied approaches, although challenges in implementing differentiated learning remained. In conclusion, the auditory learning style dominates and positively contributes to students’ mathematics achievement. These findings are expected to guide teachers in developing varied instructional media aligned with students’ learning styles.